The Problem of Filing for Bankruptcy in Indonesian Law: Should the Insolvency Test Mechanism be Applied? - Fahamsyah, Ermanto; Taniady, Vicko; Saputra, Ramadhan Dwi; Rachim, Kania Venisa; Wijaya, Glenn (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2024)
The resolution of bankruptcy disputes in Indonesia presents significant challenges due to the ease with which bankruptcy can be filed against debtors, even if they are capable of continuing their business operations and repaying their debts to creditors. This issue arises from the provisions of Article 2, paragraph (1) of Law 37/2004, which stipulate only two requirements for declaring bankruptcy: the existence of a past due debt and the presence of at least two creditors. This paper aims to examine the problems associated with bankruptcy dispute resolution in Indonesia and to propose the implementation of an insolvency test mechanism as a prerequisite before a Commercial Court judge can issue a bankruptcy ruling. Additionally, the study offers a comparative analysis of the insolvency test mechanisms employed in several countries, including the Netherlands, Germany, the United States, and the United Kingdom. Utilizing a doctrinal approach, this legal research analyzes primary and secondary literature by reviewing laws and regulations pertinent to the issues at hand. The findings of this study suggest that adopting an insolvency test is a crucial policy for the bankruptcy law framework in Indonesia. The implementation of such a test could prevent the bankruptcy of debtors who are still capable of fulfilling their financial obligations. Consequently, there is a need to revise Law 37/2004 to incorporate a legal instrument for the insolvency test.